THE INFLUENCE OF THE FAMILY ENVIRONMENT ON THE NUTRITIONAL BEHAVIOUR OF SECONDARY-SCHOOL ADOLESCENTS (ON THE EXAMPLE OF WARSAW ENVIRONMENT) - Michalak, Katarzyna (Acta Scientiarum Polonorum. Oeconomia, 2005)
The aim of the empirical survey and undertaken literature studies was to assess the influence of the family environment on the selected nutritional behaviour of adolescents from secondary-school living in Warsaw. The research was conducted among 131 pupils and 79 pupils’ mothers using a questionnaire method. A test of independence c2 was executed at a significance level of p